ASCENT OF JOHN COMPANY : FROM TRADERS TO RULERS (1756-1787) - G S CHEEMA (NEW DELHI MANOHAR, 2017)
The Ascent of John Company is the story of the founding of the British empire in India.
Keywords: INDIAN HISTORY; MODERN INDIA; EAST INDIA COMPANY